Molecular subgrouping of primary pineal parenchymal tumors reveals distinct subtypes correlated with clinical parameters and genetic alterations - Pfaff, Elke; Aichmüller, Christian; Sill, Martin; Stichel, Damian; Snuderl, Matija; Karajannis, Matthias A.; Schuhmann, Martin U.; Schittenhelm, Jens; Hasselblatt, Martin; Thomas, Christian; Korshunov, Andrey; Rhizova, Marina; et al. (Acta neuropathologica, 2020)
Tumors of the pineal region comprise several different entities with distinct clinical and histopathological features. Whereas some entities predominantly affect adults, pineoblastoma (PB) constitutes a highly aggressive malignancy of childhood with a poor outcome. PBs mainly arise sporadically, but may also occur in the context of cancer predisposition syndromes including DICER1 and RB1 germline mutation. With this study, we investigate clinico-pathological subgroups of pineal tumors and further characterize their biological features. We performed genome-wide DNA methylation analysis in 195 tumors of the pineal region and 20 normal pineal gland controls. Copy-number profiles were obtained from DNA methylation data; gene panel sequencing was added for 93 tumors and analysis was further complemented by miRNA sequencing for 22 tumor samples. Unsupervised clustering based on DNA methylation profiling separated known subgroups, like pineocytoma, pineal parenchymal tumor of intermediate differentiation, papillary tumor of the pineal region and PB, and further distinct subtypes within these groups, including three subtypes within the core PB subgroup. The novel molecular subgroup Pin-RB includes cases of trilateral retinoblastoma as well as sporadic pineal tumors with RB1 alterations, and displays similarities with retinoblastoma. Distinct clinical associations discriminate the second novel molecular subgroup PB-MYC from other PB cases. Alterations within the miRNA processing pathway (affecting DROSHA, DGCR8 or DICER1) are found in about two thirds of cases in the three core PB subtypes. Methylation profiling revealed biologically distinct groups of pineal tumors with specific clinical and molecular features. Our findings provide a foundation for further clinical as well as molecular and functional characterization of PB and other pineal tumors, including the role of miRNA processing defects in oncogenesis.